Download presentation

Presentation is loading. Please wait.

Published byEbony Helling Modified over 3 years ago

1
Differentiation The original function is the y- function – use it to find y values when you are given x Differentiate to find the derivative function or ‘gradient’ function Use this to find the value of the gradient at any point x on the curve E.g. When

3
Gradient of a point or gradient of a tangent?

4
The equation of the tangent to a curve at a given point Find the equation of the tangent to the curve when x=3 Step 1: differentiate the function to get the gradient function Step 2: find the gradient of the tangent (i.e. the curve) when x=3 Step 3: find the y-coordinate when x=3 Step 4: Find the equation of the tangent (this is a straight line equation!) The Equation of a Tangent or of a Normal

5
1. Tangents a) b) 2. 3. Extension

6
1. 2. 3. 6 The Equation of a Tangent or of a Normal

7
Extension 7 The Equation of a Tangent or of a Normal

8
What is ‘normal’ in a Maths lesson?

9
The equation of the normal to a curve at a given point Find the equation of the normal to the curve at the point where x is -1 Step 1: differentiate the function to get the gradient function Step 2: find the gradient of the tangent (i.e. the curve) when x= -1 Step 4: find the y-coordinate when x= -1 Step 5: Find the equation of the normal (this is a straight line equation!) Step 3: find the gradient of the normal when x= -1 9 The Equation of a Tangent or of a Normal

10
Normals 10 The Equation of a Tangent or of a Normal

11
Gradient of a Curve Investigating further Copy this curve onto your whiteboard. Mark on to the graph where it has a positive gradient. Mark where it has a negative gradient If y stands for the distance travelled by a car and x stands for time, when is the car stationary?

Similar presentations

OK

Differentiation. f(x) = x 3 + 2x 2 – 3x + 5 f’(x) = 3x 2 + 4x - 3 f’(1) = 3 x 1 2 + 4 x 1 – 3 = 3 + 4 – 3 = 4 If f(x) = x 3 + 2x 2 –

Differentiation. f(x) = x 3 + 2x 2 – 3x + 5 f’(x) = 3x 2 + 4x - 3 f’(1) = 3 x 1 2 + 4 x 1 – 3 = 3 + 4 – 3 = 4 If f(x) = x 3 + 2x 2 –

© 2018 SlidePlayer.com Inc.

All rights reserved.

Ads by Google

Ppt on 2nd world war youtube Cathode ray tube display ppt on tv Ppt on waves tides and ocean currents diagram Ppt on verb forms Ppt on 3 phase ac circuits Ppt on shell scripting cheat Ppt on cleanliness in schools Ppt on area of a parallelogram Ppt on id ego superego examples Display ppt online